ORGANIZATION AS A CRITERION FOR ACADEMIC WRITING EVALUATION POSSIBLE PATTERNS OF ORGANIZATION IN EXPOSITORY WRITING - Gulchehra Agzamkhanova; Yaroslav Vladimirovich Golovko (Western European Studies, 2024)
In order to ensure the clarity of expressed message in academic writing, writers not only need to be proficient in grammar and mechanics and have rich vocabulary stock, but also be able to sequence their ideas in such a way as to enhance readers’ understanding. Different genres and subgenres of academic writing clearly require different approaches to the arrangement of ideas, or organizational patterns. This article substantiates the significance of organization in academic writing and provides three suggested organizational patterns for the narrative, descriptive, and process subgenres of expository academic writing.
Keywords: academic writing; expository; argumentative